The Oxford handbook of international human rights law - Shelton, Dinah (Oxford : Oxford University Press, 2013)
This handbook provides an authoritative and original overview of one of the key branches of international law. Forty contributors comprehensively analyse the role of human rights in international law from a global perspective, examining its origins and principles, and measuring its impact on the world.
Specialized.
Description based on online resource; title from home page (viewed on December 2, 2013).
Keywords: Human rights; International law; Law; International law